The study of swimming propulsion using computational fluid dynamics - Marinho, D.; Leal, L.; Reis, V.; Alves, F.; Vilas-Boas, J. P.; Rouboa, A.; Silva, A. (12th Annual Congress of the European College of Sport Science, Jyväskylä, Finland - July 11-14th 2007, 2007)
The generation of propulsive forces in human swimming has been studied recently using numerical simulation techniques with computational fluid dynamics (CFD) models (Bixler and Riewald, 2002; Rouboa et al., 2006). However, some limitations still remain, regarding the geometrical representation of the human limbs. Therefore, the aim of this study was to determine the propulsive force in a 3-D hand/forearm model using CFD. Methods The CFD analysis consisted in the use of a mesh of cells that simulates the flow around the considered model. The whole domain was meshed with 400.000 trapezoidal elements of 4 nodes each. Numerical simulations for the whole computational steady domain were calculated in the three dimensions with the commercial code fluent. Models used in the simulations were created in CAD, based on realistic dimensions of a right adult human hand/forearm. The governing system of equations considered was the incompressible Reynolds averaged Navier-Stokes equations with the standard k-epsilon model (Moreira et al., 2006). Flow speeds were chosen to be within or near the range of typical hand speeds during freestyle swimming underwater path: from 0.50 m/s to 4.00 m/s. Angles of attack of hand/forearm model of 0o, 45o e 90o, with an angle of orientation of 0o (thumb as the leading edge) were used for the calculations. The measured forces on the hand/forearm model were decomposed into drag and lift components. The combined hand and forearm drag (CD) and lift (CL) coefficients were calculated. Results The magnitude of CD and CL remained constant throughout the flow speeds tested. Angles of attack of 0o, 45o and 90o produced, respectively, CD values of 0.35, 0.63 and 1.10 and CL values of 0.18, 0.32 and 0.05. Discussion CD was the main responsible for propulsion, with the maximum value of force production corresponding to an angle of attack of 90o, as expected. CL has a residual influence in the generation of propulsive force by the hand/forearm segment for angles of attack of 0o and 90o, but it is important with an angle of attack of 45o. These data confirm experimental studies reporting reduced contribution of lift component to the overall propulsive force generation by the hand/forearm in front crawl swimming, except for the insweep phase, when the angle of attack nears 45o (Berger et al., 1995; Sanders, 1999).